The Space of Harmony: Optimizing Dialogue and Music Performances in Strengthening Religious Moderation in Manado - Purba, Berehme Adyatmo; Febriyando (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study aims to examine the role of the “Menyatu dalam Harmoni” music performance, a collaboration between the State Christian Institute of Manado and the State Islamic Institute of Manado, in fostering interfaith harmony through the promotion and dessemination of religious moderation values. The research method employed was a descriptive qualitative case study. Data were collected through semi-structured interviews with organizers, musicians, religious leaders, and audience members; participant observation during the event; and document analysis of published media, performance materials, and archives. Findings indicate that the performance served not merely as entertainment but as a social interaction space that built mutual trust, strengthened empathy, and nurtured collective awareness of the importance of interfaith cooperation. The discussion highlights that art-based approaches can transcend religious identity boundaries and act as effective bridges for dialogue, contributing strategically to the strengthening of social harmony.